Synthesis of 7-Azidofurazano[3,4-b]tetrazolopyrazine and Isomer's Structure in Different Polarity Solvents - Guo, Tao; Liu, Min; Jiang, Jun; Qiu, Shao-Jun; Ge, Zhong-Xue (Asian Journal of Chemistry, 2013)
7-Azidofurazano[3,4-b]tetrazolopyrazine (FSZPA) was synthesized via methoxylation, nitration hydrazinolysis and azidation, using 2,6- dichloropyrazine as a starting material. The structures of 7-azidofurazano[3,4-b]tetrazolopyrazine and intermediates were identified by FTIR, NMR and elemental analysis. 15N and 13C NMR spectra showed three isomer forms resulting from the reversible opening and closing between asido and tetrazole depending on polarity of the solvents.